2013
DOI: 10.5812/ircmj.2312
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder (PTSD) Following Childbirth: Prevalence and Contributing Factors

Abstract: BackgroundChildbirth might be a traumatic event for some women.ObjectivesThis study was conducted with the objective of investigating the prevalence of Post-Traumatic Stress Disorder (PTSD) following childbirth.Patients and MethodsThe study was designed using a descriptive correlation scheme. The participants were selected from the women referred to the healthcare centers affiliated with Zahedan University of Medical Sciences, Zahedan, Iran. Personal interviews were conducted with 600 women who were 6-8 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…In the present study, the prevalence of PTSD following childbirth was 26,7% which was in line with the previous Iranian studies (172,%-39%) [6,7]. But this prevalence is high compared to developed countries [2][3][4][5].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the prevalence of PTSD following childbirth was 26,7% which was in line with the previous Iranian studies (172,%-39%) [6,7]. But this prevalence is high compared to developed countries [2][3][4][5].…”
Section: Discussionsupporting
confidence: 92%
“…Other studies also supported the effect of infant's restlessness and crying and problem in taking care of the infant on developing PTSD following childbirth [6,7]. Other studies have also reported a significant relationship between infant's crying and postpartum depression [22,25].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Anxiety is one of the most common adjustment disorders in all societies, which has a global prevalence of 14% and a prevalence of 20.8% in Iran 1, 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the prevalence of stress and anxiety during pregnancy as 6% to 78%; that is, 6% of the population is reportedly exposed to high levels of stress and 78% is exposed to low or moderate levels (7)(8)(9). Stress during pregnancy can be associated with adverse pregnancy outcomes such as miscarriage, fetal weight loss, increased stress hormone levels, chronic hypertension, premature birth, infant mortality, changes in endocrine secretion, changes in hypothalamic-pituitary function, suppressed immune system, changes in the number of lymphocytes and reduced CD4/CD8 ratio, nausea, vomiting, preeclampsia, and some degree of mental disorder (10)(11)(12)(13)(14)(15)(16). The complications associated with pregnancy-induced stress are a leading cause of maternal perinatal mortality (17).…”
Section: Introductionmentioning
confidence: 99%